More Severe Hypercoagulable State in Acute COVID-19 Pneumonia as Compared With Other Pneumonia - Spiezia, Luca; Campello, Elena; Cola, Marco; Poletto, Francesco; Cerruti, Lorenzo; Poretto, Anna; Simion, Chiara; Cattelan, Annamaria; Vettor, Roberto; Simioni, Paolo (Mayo Clinic proceedings. Innovations, quality & outcomes, 2020)
To conduct a comprehensive evaluation of coagulation profiles—via traditional and whole blood thromboelastometry tests—in coronavirus disease 2019 (COVID-19)–positive vs COVID-19–negative patients admitted to medical wards for acute pneumonia. We enrolled all consecutive patients admitted to internal medicine wards of Padova University Hospital between 7 March and 30 April, 2020, for COVID-19–related pneumonia (cases) vs non–COVID-19 pneumonia (controls). A group of healthy individuals acted as baseline for thromboelastometry parameters. Fifty-six cases (mean age, 64±15 years; male/female, 37/19) and 56 controls (mean age, 76±11 years; male/female, 35/21) were enrolled. Cases and controls exhibited markedly hypercoagulable thromboelastometry profiles vs healthy individuals, mainly characterized by a significantly shorter propagation phase of coagulation (clot formation time) and significantly increased maximum clot firmness (P<.001 for all comparisons). Patients with COVID-19 pneumonia had significantly shorter clot formation time and higher maximum clot firmness (P<.01 and P<.05, respectively, for all comparisons) than did controls. Patients admitted to internal medicine wards for COVID-19 pneumonia presented a markedly prothrombotic state, which seems peculiar to COVID-19 rather than pneumonia itself.